INTERPERSONAL COMMUNICATION PATTERNS OF STUDENTS FROM PALEMBANG IN RW 04 KAYU JATI WITH PARENTS ON WHATSAPP MEDIA - Alda Sriwah Yuni; RR Rosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Communication between migrant students and their parents plays an important role in maintaining family relationships despite geographical distance. WhatsApp is one of the most widely used communication media because it provides various features, such as text messaging, voice messaging, voice calls, and video calls. The use of WhatsApp helps migrant students and their parents stay connected in their daily lives. This study aims to identify the interpersonal communication patterns of migrant students from Palembang living in RW 04 Kayu Jati with their parents through WhatsApp, to understand the forms of interaction used, and to identify the obstacles encountered in the communication process. This study employed a descriptive qualitative method, with data collected through interviews, observation, documentation, and triangulation. The findings indicate that communication between migrant students and their parents is carried out regularly, openly, and supportively. This communication is used to exchange information, maintain emotional closeness, and provide moral support. The obstacles identified include internet network disruptions, delays in responding to messages, and misunderstandings in interpreting message content. However, these obstacles do not reduce the intensity of the communication.